When Passion Does Not Change, but Emotions Do: Testing a Social Media Intervention Related to Exercise Activity Engagement - Berg, Silje; Forest, Jacques; Stenseng, Frode (Frontiers in Psychology, 2020)
Grounded in self-determination theory and the dualistic model of passion, the present study tested whether a social media intervention could promote harmonious passion and positive emotions related to exercise activities. A 4-week intervention managed through an Instagram™ account was designed to promote more harmonious passion and less obsessive passion, as well as more positive emotions and less negative emotions related to participants’ favorite exercise activities. A web-based questionnaire was distributed to 518 young adults (mean age 26.5) before and after the intervention. Participants were randomly assigned to an intervention group (N = 226) or control group (N = 292). The intervention did not predict change in passion for the activity. However, the intervention predicted more positive emotional outcomes from the activity, statistically controlled for emotions reported at baseline and negative emotions reported at follow-up. Results indicate that digital platforms may be relevant in promoting more physical activity in the population, through the facilitation of more positive emotions related to exercise.